An investigation into microstructure, tribological and mechanical properties of cold sprayed Inconel 625 coatings - Wu, Kaiqiang (2022)
In this study, Inconel 625 coatings were successfully deposited on 6061 aluminum alloy using a high-pressure cold spray process. The microstructure, mechanical and tribological properties of the coatings were systematically studied. The cold sprayed Inconel 625 coatings had a low porosity level due to the severe plastic deformation of the splats. EBSD analyses revealed that grain refinement occurred within the coatings and substrates (near the substrate-coating interface), which could be attributed to strain accumulation and fragmentation process. Good adhesion strength of above 57.0 MPa was achieved between the coatings and substrates. Nano-hardness and micro-hardness values were higher than those of bulk Inconel 625 and were uniform along the thickness of the coatings. The effects of normal load and sliding velocity on the tribological properties of cold sprayed Inconel 625 coatings were investigated by sliding wear tests. The wear results demonstrated that both increased sliding velocity and normal load led to higher specific wear rates, which could result from the combined effects of tribo-film delamination, adhesive wear, abrasive wear, and thermal softening. Lower coefficients of friction of the coatings measured under 5 N compared to those measured under 2 N with the same sliding velocity could be explained by transition of wear mechanisms as well as larger coverage of tribo-film on the wear tracks.